Advanced Techniques for High-Temperature Measurements - Alfarraj, Bader A.; Aljohani, Sama Badr; Alshunaifi, Ibrahim A.; Alqahtani, Naif B. (Scientific Research, New Technologies and Applications Vol. 2, 2024)
This chapter briefly discusses various techniques for the measurement of temperature. The study especially focuses on a pyrometer system to determine temperature. Aims: The aim of this study is to develop a two-wavelength pyrometer system capable of accurately measuring high surface temperatures in turbulent flames. Methodology: A pyrometer system combines electronic and optical instruments to detect low-level signals of radiation measurements. Temperature measurements were also performed using Planck’s model, and the results were compared using the logarithmic assumption. Variable optimization of the instruments, validation of the data, and calibration of the pyrometer system were investigated to enhance precision. The response time between temperature readings is within 785 µs. Results: The developed pyrometer system exhibited high stability (±2.99°C at 1600°C) and reduced error (less than 2.29% for Si sensor). In addition, the error of the temperature measurement was reduced from 5.33% to 0.86% at 850°C by using Planck’s model compared with using logarithmic assumption. The spectral pyrometry system was also used to measure temperature. It was found that the spectral pyrometry can be used to determine temperature measurements.